Differential excitatory vs inhibitory SCN expression at single cell level regulates brain sodium channel function in neurodevelopmental disorders. (January 2020) - Du, Juanjiangmeng; Simmons, Sean; Brunklaus, Andreas; Adiconis, Xian; Hession, Cynthia C.; Fu, Zhanyan; Li, Yinqing; Shema, Reut; Møller, Rikke S.; Barak, Boaz; Feng, Guoping; Meisler, Miriam; et al.
Abstract: The four voltage-gated sodium channels SCN1/2/3/8A have been associated with heterogeneous types of developmental disorders, each presenting with disease specific temporal and cell type specific gene expression. Using single-cell RNA sequencing transcriptomic data from humans and mice, we observe that SCN1A is predominantly expressed in inhibitory neurons. In contrast, SCN2/3/8A are profoundly expressed in excitatory neurons with SCN2/3A starting prenatally, followed by SCN1/8A neonatally. In contrast to previous observations from low resolution RNA screens, we observe that all four genes are expressed in both excitatory and inhibitory neurons, however, exhibit differential expression strength. These findings provide molecular evidence, at single-cell resolution, to support the hypothesis that the excitatory/inhibitory (E/I) neuronal expression ratios of sodium channels are important regulatory mechanisms underlying brain homeostasis and neurological diseases. Modulating the E/I expression balance within cell types of sodium channels could serve as a potential strategy to develop targeted treatment for NaV -associated neuronal developmental disorders. Highlights: Transcriptome assays reveal distribution of SCN expression at single-cell level. SCNs are found in excitatory & inhibitory cells with different expression strength. SCN expression ratios regulate underlying brain homeostasis and neuronal disease.